O-026 Balloon assisted coiling of intracranial aneurysms: complication comparison between non-assisted and balloon assisted procedures. (16th November 2010) - Perl, J; Fease, J; Tubman, D; Crandall, B
Abstract : Background and purpose: There is still a question in the current literature as to whether the addition of balloon assistance in intracranial aneurysm embolization procedures increases thromboembolic and intraoperative perforation complications. The purpose of this study was to determine if balloon assisted coiling (BAC), given the use of an additional device, increases complications compared with conventional coiling of intracranial aneurysms. Methods: Between June 2002 and February 2010, 845 consecutive intracranial aneurysm embolization procedures were assessed. Of these procedures, 640 (207 ruptured) procedures had a high compliant balloon (Hyperform (73.8%) or Hyperglide (25.8%); eV3 Corp) inserted during the procedure; 205 (127 ruptured) procedures had no adjunctive devices inserted during the course of the procedure. Procedures utilizing stent assistance were excluded from the study. Procedures were performed by three different interventionalists at a single center. Procedural thromboembolic complications, intraoperative perforations, hospital course complications and Glasgow Outcome Score were reviewed and recorded retrospectively and prospectively. Comparisons between the techniques were also made between ruptured and unruptured aneurysms. Results were analyzed using the Student t test; p values <0.05 were considered statistically significant. Results: With BAC, 88.8% of procedures had no complications whatsoever (85.0% ruptured, 90.5% unruptured) and with conventional coiling, 84.9% (80.1% ruptured, 92.3% unruptured) (p=0.168) of procedures had no complications. Thromboembolic complications with clinical sequelae occurred more during conventional coiling (7.3%; 15/205) than BAC (1.1%; 7/640) (p=0.001). Intraoperative perforation occurrences were not statistically significantly different (2.8% BAC versus 1.5% conventional coiling; p=0.20)). Of the intraoperative perforations with BAC, only 38.9% (7/18) occurred while the balloon was inflated. In 33.3% (6/18), the balloon was inflated only after perforation by coil or microcatheter. In 11.1% (2/18), the balloon was only inserted after the perforation had occurred, 5.6% (1/18) occurred during angioplasty and in 11.1% (2/18) extravasation was seen immediately after procedure termination. In the BAC procedures, 94.8% had no hospital course complications (90.8% ruptured, 96.8% unruptured) and in conventional coiling procedures, 85.9% (78.0% ruptured, 98.7% unruptured) had no hospital course complications. Glasgow Outcome Score in ruptured and unruptured aneurysms showed no statistically significant difference in BAC procedures compared with conventional coiling procedures. Conclusion: The use of balloon assistance in intracranial aneurysm embolization procedures does not increase technical or clinical complications compared with embolization procedures without balloon assistance.